2018
DOI: 10.1021/acs.jpcc.8b03874
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Antireflective Iridium Oxide Coating for Water Oxidation

Abstract: Iridium oxide (IrO x ) is one of the best catalysts for the aqueous oxygen evolution reaction (OER), and its activity is greatly impacted by surface characteristics. By reactively sputtering in a high O 2 flow-rate environment, vertically oriented IrO x nanoplatelets grow several hundred nanometers high exhibiting large surface areas and antireflective optical properties across the visible spectrum. The nanoplatelet IrO x surface is electrochemically compared to other morphologies of IrO x surfaces for OER act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…[15][16][17] Theoretical studies of Ir activity are complicated by the well-known fact that at the sustained, high potentials of OER, Ir-based catalysts oxidize and often contain the rutile phase with various percentages of facet families. 15,[18][19][20] Pavlovic et al observed at potentials >1.2 V, Raman spectra of their hydrous iridium oxide samples begin to display peaks for the E g (550 cm −1 ) and B 2g modes (720 cm −1 ) specific to rutile iridium oxide; by 1.8 V, these peaks are strong and sharp. Since the lifetime of commercial proton exchange membrane electrolyzers is typically ∼5 years, operating at 1.8-2.0 V, some rutile iridium oxide is most likely present in the catalyst 20 so more complex views of what the active materials and facets are in the catalysts need to be considered.…”
mentioning
confidence: 97%
“…[15][16][17] Theoretical studies of Ir activity are complicated by the well-known fact that at the sustained, high potentials of OER, Ir-based catalysts oxidize and often contain the rutile phase with various percentages of facet families. 15,[18][19][20] Pavlovic et al observed at potentials >1.2 V, Raman spectra of their hydrous iridium oxide samples begin to display peaks for the E g (550 cm −1 ) and B 2g modes (720 cm −1 ) specific to rutile iridium oxide; by 1.8 V, these peaks are strong and sharp. Since the lifetime of commercial proton exchange membrane electrolyzers is typically ∼5 years, operating at 1.8-2.0 V, some rutile iridium oxide is most likely present in the catalyst 20 so more complex views of what the active materials and facets are in the catalysts need to be considered.…”
mentioning
confidence: 97%
“…In 2018, David et al prepared an iridium oxide nanosheet. [60] The SEM images show the morphology of nanoplatelets with the thickness of 380 nm. The XRD pattern reveals its rutile phase structures.…”
Section: Other 2d Iridium Oxidementioning
confidence: 99%
“…47 Baker et al reported a IrO x nanoarray synthesized by reactive sputtering in an oxygen atmosphere. 48 However, both methods require specific equipment and complex procedures. The development of a more facile method is desired but is challenging.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Berlinguette and co-workers prepared a self-supported amorphous IrO x film by the light-induced decomposition of iridium­(III) acetylacetonate . Baker et al reported a IrO x nanoarray synthesized by reactive sputtering in an oxygen atmosphere . However, both methods require specific equipment and complex procedures.…”
Section: Introductionmentioning
confidence: 99%